Local recurrence after endoscopic mucosal resection of nonpedunculated colorectal lesions: systematic review and meta-analysis - Belderbos, Tim D. G.; Leenders, Max; Moons, Leon M. G.; Siersema, Peter D. (Endoscopy, 2014)
Background and study aims: Local recurrence has been observed after endoscopic mucosal resection (EMR) of nonpedunculated colorectal lesions. The indications for follow-up colonoscopy and the optimal time interval are currently unclear. The aims of this systematic review were to assess the frequency of local recurrence after EMR, to identify risk factors for recurrence, and to provide follow-up recommendations.Methods: A literature search was performed in PubMed, EMBASE, and the Cochrane Library. EMR was defined as endoscopic snare resection after submucosal fluid injection for removal of nonpedunculated adenomas and early carcinomas. Local recurrence was subdivided into early recurrence (detected at the first follow-up colonoscopy) and late recurrence (detected after ≥ 1 previous normal colonoscopy). A random effects meta-analysis was performed to calculate the pooled estimate of risk of recurrence.Results: A total of 33 studies were included. The mean recurrence risk after EMR was 15 % (95 % confidence interval [CI] 12 % – 19 %). Recurrence risk was higher after piecemeal resection (20 %; 95 %CI 16 % – 25 %) than after en bloc resection (3 %; 95 %CI 2 % – 5 %; P < 0.0001). In 15 studies that differentiated between early and late recurrences, 152/173 recurrences (88 %) occurred early. In four studies with follow-up at 3, 6, and ≥ 12 months, 19/25 (76 %) recurrences were detected at 3 months, increasing to 24 (96 %) at 6 months. In multivariable analysis, only piecemeal resection was associated with recurrence (3 of 3 studies).Conclusion: Local recurrence after EMR of nonpedunculated colorectal lesions occurs in 3 % of en bloc resections and 20 % of piecemeal resections. Piecemeal resection was the only independent risk factor for recurrence. As more than 90 % of recurrences are detected at 6 months after EMR, we propose that 6 months is the optimal initial follow-up interval.